2012
DOI: 10.5625/lar.2012.28.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of caveolins and myosin heavy chains in response to forced exercise in rats

Abstract: Exercise training can improve strength and lead to adaptations in the skeletal muscle and nervous systems. Skeletal muscles can develop into two types: fast and slow, depending on the expression pattern of myosin heavy chain (MHC) isoforms. Previous studies reported that exercise altered the distribution of muscle fiber types. It is not currently known what changes in the expression of caveolins and types of muscle fiber occur in response to the intensity of exercise. This study determined the changes in expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To our knowledge, there are no data that show changes in cholesterol and Cav-1 levels in liver and skeletal muscle mitochondria after exercise. However, Park and colleagues showed that there are changes in the Cav-1 concentrations in skeletal muscles [ 25 ] and in rat brain tissues following training [ 26 ]. The Cav-1 in the skeletal muscle is a fibre and exercise-specific [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no data that show changes in cholesterol and Cav-1 levels in liver and skeletal muscle mitochondria after exercise. However, Park and colleagues showed that there are changes in the Cav-1 concentrations in skeletal muscles [ 25 ] and in rat brain tissues following training [ 26 ]. The Cav-1 in the skeletal muscle is a fibre and exercise-specific [ 12 ].…”
Section: Discussionmentioning
confidence: 99%